Вы находитесь на странице: 1из 12

6.

.
1. . . .
6.1-6.17
:
6.1 z = x + y + x y
6.2 z = 1 x 2 y 2
6.3 z =

1
x

6.4

+ y 2 1

6.5 z = ln y 2 4 x + 8

z = 1 x 2 + 1 y 2

6.6

z = ln x 2 + 4 y 2 2 x 3
1
6.7 z =
2
x 16 ( y 2 + 1)

6.8 z =

ln x ln y
1x y

6.9 z = arccos( x + y )

6.10 z = arcsin

6.11 z = ln x ln sin y

6.12

6.13 u =
6.15

1
1x y2 z2
u =1

6.14

x +1

u = ln 36 36 x 2 9 y 2 4 z 2

y +1

z =

x
x+y

y sin x

u = 16 x 2 z 2

6.16

6.17 u =

1
z x2 y2

6.18 u = arccos 2 x 2 y 2 z 2
6.19. :
) z = x + y ; ) z = x 2 + y 2 ; )

z =x2 y2 ;

.
6.20 :

83

) z =

1
2

x + 2y2

xy

lim

) x0 3

xy + 9

y 0

x2 + y2

lim

x 2 + y 2 +1 1

x 0
y 0

x2

sin( xy )
lim
x
) x
0

y
2

1 x +y

lim 1 + x

y
1

6.21 :
1

) z =
) z =

+y

x+y
3

x + y3

xy

) z = x + y ;

) z = ln( 1 x 2 y 2 ) .

2.
6.22-6.32
, z xy
, z yy
:
z x , z y , z xx
6.22 z = x 3 + y 3 3 xy
6.23 z = x 4 + y 4 4 x 2 y 2
6.25 z =

6.24 z = xy + y x
6.27 z =

cos( x 2 )
y

z = ln x + y 2

x
y

6.26 z =

6.28 z = tg x 2 y

y
6.30 z = arctg
x

x
x

+ y2

6.29

6.31 z = x y

x+y

6.32 z = arctg 1 xy
6.33-6.34
, u xy
, u xz
:
u x , u xx
6.33 u =

x
6.34 u =
y

x2 + y2 + z2

84

6.35
)

2 z
2 z
=
,

x
y

y
x

z = x 2 2 xy 3 y 2 ;

)
3

6.36

y x

z =arccos

x y

z
xy 2

y
z = arctg
x
6.37-6.40 :

3 z
, z = e y 2x
yx 2

6.37

6.38

3 z
,
xy 2

z = ln( x 2 + y 2 )

3 z
, z = x ln( xy )
x 2 y
3 z
2 y 2 x
z =cos
e

6.40

2 ,
yx
6.39

3 .
6.41-6.46
:
y

6.41 z = x y
6.43 z =ln ( x 2 + y 2 )

6.42

6.45 u = xy + yz + zx

6.46 u =

6.47

z =x + y

6.48
z=

xy
2

x y2

z=

x2 +y2

6.44 z = e xy
z
2

x + y2


y = 4, x = 0,1 y = 0,2.
+ y 2 x = 3,

x = 2,

y =1,

6.49 :

85

x = 0,01

y = 0,03 .

) ln( 0,09 3 +0,99 3 )

) 1,02 4,05
3

1,02

+0,05

0,02

1,04 1,99 +ln 1,02

sin 29 tg 46

) 5
)
+ 2,03

) sin 28 cos 61

) ln( 3 1,03 + 4 0,98 1)

6.50
x = 6 y =8 ,
2 ,
5 ?
6.51 =60
=1 .
R = 20 c ,
?
6.52 : = 2 ,
b = 3 , = 6 .
, 2 , b
1c , 3 .
6.53 :
R=2,5 , =4 l=1.
,
.
6.54 R=20 , r=10
h=30 .
1
V = H ( R 2 + rR + r 2 ) , R 2, r
3
3, h 1 ?
6.55 :
)

z=

2
x
e x ;
y

P (0;1)

z = 4 y 2 + sin 2 ( x y );

)
P (0;0)

4. .
.
86

dz
,
dt
) z = e 2 x 3 y ,
x =tgt , y =t 2 t
y
) z = arctg
,
x = e 2t +1, y = e 2t 1
x
) z = x y ,
x = ln t , y = sin t
) z = arcsin( x y ) ,
x =3t , y = 4t 3
6.57 du dt ,
) u = x 2 y y 2 z + xz 2 ,
x = sin t , y = cos t , z = tgt
) u = yz x ,
x = e t , y = ln t , z = t 2 1
z
dz
6.58

,
x
dx
) z = ln e x + e y ,
y = x 3 3 + x

6.56

x +1

,
y

) z = arctg

y = e ( x +1)

) z = tg (xy ) ,
y = e x
) z =arcsin( x y ) ,
y = x 2 +1

z
z
6.59

,
y
x
) z = u 2 ln v
u = y x ; v = x 2 + y 2
2
2
) z =u v v u ,
u = x cos y , v = y sin x
6.60 dz ,
) z = f (u , v ),

2y

u = x + y ;

v = x 2 3y

) z = f (u ,v),
u = ln x 2 y 2 ; v = xy 2
6.61 ,
: ) z = ln( x 2 + y 2 ) ,

2 z
x 2

2 z

1 1

,
y
x

) z = ln

x 2

87

2 z
y 2

=0 .

2 z
1
=
xy
x2

2 z

xy

) z = x y ,

x 2

+2

2 z
2 z
2
+
=
2
xy
x

y
y

.
)
2

z = x e y x ,

z
z
z
z
y
+ 2
+
=0 .

xy
y
y 2
x

6.62 , ,
:
z
z
) y x x y =0 ,
z =( x 2 + y 2 ) .
y
1 z
1 z
z
) x x + y y = 2 ,
z =
.
2
y
( x y 2 )
z
z
2
2
) x x + y y = z x y , z = x ( y x ) x 2 y 2 .
z

y2
+ ( xy ) .
3x
6.63 y x y = f (x) ,
2
2
) x x xy y + y = 0 ,

z =

:
) x 3 y y 3 x = a 4

sin( xy ) e xy y x 2 = 0

y
) ln x 2 + y 2 = arctg
x
y
) y x = x y ( x y )
) y = 2 x arctg
x
6.64
y = f (x) , :

x 2 e 2 y y 2 e 2x = 0

dy d 2 y
,
dx dx 2

dy d 2 y d 3 y
,
,
dx dx 2 dx 3

x + y =e xy ;

x 2 + 2 xy + y 2 4 x + 2 y 2 = 0

88

6.65 z x , z y
z = f ( x, y ), :
) z 3 3 xyz = a 3
) x 2 2 y 2 + z 2 4 x + 2 z 5 = 0
xy
= 0.
) e z xyz =0
) z ln( x + z )
z
6.66 dz z = f ( x, y ),
M 0 ( x 0 , y 0 ) , :
) z 3 xz + y = 0,
z

) x z = z ln y ,
6.67

M 0 (3, 2, 2)
M 0 (1, 1, 1)

dz

x
y

z = f ( x, y ), , :
) xyz = x + y + z ;
) z = e x + y + z ;
)

z
x
= ln
y
+1 ;
z

) z = x + arctg
u

6.68

g ra du

y
.
z x

l ,

g ra du |

M 0 ( x 0 , y 0 , z 0 ) :


l = 2i + j k ,
) u = x +ln( z 2 + y 2 ) ,
M 0 ( 2,1,1)

u = y ln( 1 +x 2 ) arctgz

M 0 (0,1,1)

u = xy x z


l =5i + j k ,

M 0 ( 4,3,1)

u =z 2 +2 arctg ( x y )

l = 2i 3 j 2k ,

l = i + 2 j 2k ,

M 0 (1,2,1)
x

6.69 z =arcsin x + y
A(1, 1) B (3, 4) .
89

6.70 z1 = x 2 y 2
z 2 = x 3 + y 3 3xy M 0 ( 4, 3) .
z
6.71
M 0 ( x 0 , y 0 ) , :
l max

) z = xy 2 3 x 4 y 5 , M 0 (1, 1) ;
) z =( x + y ) y ,
M 0 ( 2, 1) .
5. .
6.72
M 0 ( x 0 , y 0 , z 0 ) :
z = x 2 + y 2 , M 0 (1, 2, 5)
z = ( x y ) 2 x + 2 y , M 0 (1, 1, 1)

) z = x 2 + y 2 xy , M 0 ( 3,4,17 )
) z = arctg ( y x ), M 0 (1, 1, 4).
6.73
M 0 ( x 0 , y 0 , z 0 ) :
) x 3 + y 3 + z 3 + xyz = 6, M 0 (1, 2, 1)
) e z z + xy = 3, M ( 2, 1, 0)
)
0

z = y + ln( x z ) , M 0 (1, 1, 1)

2 x z + 2 y z = 8, M 0 (2;2;1)

6.74 z = 4 x xy + y 2

4 x + y + 2 z + 9 = 0.

6.75

x 2 z 2 2x + 6 y = 4


x + 2 y z +1
= =
.
,
1
3
4
6.76. :
) z = x 2 + y 2 ;
) z =1 ( x 2 + y 2 ) ;
) z = x 2 y 2 ;
) z = ln( 1 + x 2 + y 4 ) .

90

6.77. E x (z ) E y (z )
z ( x, y ) M 0 ( x 0 , y 0 ) :
) z = 2 x 2 y + 3xy 2 + x 3 , M 0 (1, 1) ;
) z = x y ,
M 0 ( 2, 3) .
6.78 )
; ) ; )
,
Q ( K , L ) , Q - , K -
, L - ,
:
1) Q =K 1 2 L1 3 , =10 4 , L =10 3 .
2) Q =K 2 3 L1 4 , =10 3 , L = 5 4 .
6 .
6.79
:
) z = x 2 + 2 xy + 3 y 2 6 x 2 y 2; M 0 (2, 1)
) z = 2 x 2 xy y 2 6 x 3 y;
3

) z = x 2 y + 3 xy ;
3

M 0 (1, 2)

M 0 (1, 2)
2

) z = x 5 x xy + y + 10 x + 5 y;
2

) u = ( x + y + z ) ;
2

M 0 ( 2, 1)

M 0 (1, 1, 2)

) u = x + 3 z 2 yz 3 z; M 0 (0, 1, 2)
6.80
z ( x, y )
:
1

) z = x y ; M 0 ( 2, 1)

) z = x + y ;

M 0 ( 2, 2)

) z = arctg ( x y ); M 0 (1, 1)
6.81 z ( x, y )
:
sin x

z = e x cos y

) z = cos y
7
)

91

6.82-6.100
:
6.82 z = 3 + 2 x y x 2 + xy y 2 6.83
z = 3 x + 6 y x 2 xy + y 2 6.84 z = x 2 xy + y 2 2 x + y
6.85 z = x 2 + xy + y 2 12 x 3 y
6.86 z = xy 2 (12 x y ) ( x > 0, y > 0)
6.87
z = x 3 + y 3 3 xy

6.88 z = xy +

50 20
+
(x>0,y>0) 6.89
x
y

z =x 2 + y 2 2 ln x 18 ln y

z = x 2 + xy + y 2 4 ln x 10 ln y

6.90

6.91

z =8 x + x y + y

6.92 z = x + y 2 e x 2
z =2 x + x

6.94 z
z =x

6.96
6.97
6.98
6.99
u=

6.93

y +y

=3 x y + y 3 12 x 15 y +3

6.95

+8 y 3 6 xy +1

u =8 6 x + 4 y 2 z x 2 y 2 z 2
u = x 2 + y 2 z 2 4x + 6 y 2z
u = x 2 + y 2 + z 2 4x + 6 y 2z

u = xyz (16 x y 2 z )
2

6.100

y
256
x
+
+
+ z2
x
y
z

6.101-6.108
:
6.101 z = xy
x + y 1 = 0
2
2
6.102 z = x y
2 x y 3 = 0
z
=
5

3
x

4
y
6.103
x 2 + y 2 = 25
6.104 z = x + 2 y
x 2 + y 2 = 5
6.105 z =1 x +1 y
x + y = 2
z
=
1
+
1
x
+
1
y
6.106
1 x 2 +1 y 2 =1 8
6.107 u = 2 x + y 2 z x 2 + y 2 + z 2 = 36
x + 2 y + 3 z =12
6.108 u = xy 2 z 3

( x > 0, y > 0, z > 0) .


92

6.109-6.111
:
6.109 ) z = xy + x + y
D: 2 x 2, 2 y 4
) z = x 2 y + 5
D: x 0, y 0, x + y 1
z
=
x
+
y
)
D: x 2 + y 2 4
6.110 ) z = x 2 + y 2 4 x
D: 2 x 1, 1 y 3
z
=
xy

(
6

y
)
)
D:
x 0, y 0, x + y 12

)
6.111 )

z =x2 y2
z =x

D: x 2 + y 2 4
D: 0 x 1, 0 y 2

+ 2 xy 4 x + 8 y

) z = x 2 y ( 4 x y )

D:

x 0, y 0, x + y 6

) z = (2 x 2 + 3 y 2 ) e x2 y 2 D: x 2 + y 2 1
6.112 ,
, :
) S;
) a.
) d .
) R.
6.113 ,
, V.
6.114
, ( ) S.
6.115
, S.
6.116. M 0 ( x 0 , y 0 ) ,
x = 0 , y =0 , x + 2 y 16 = 0
.
6.117 ABC A(0, 1) , B (3, 4) ,
C (5, 2)
M 0 ( x 0 , y 0 )


.
6.118 x y
p q .. x 0 y 0
,
93

: ) z = x 2 + xy + y 2 , p =8 ,
q =10 ;
) z =3 x 2 2 + 2 xy + y 2 , p =32 ,
q = 24 .
6.119 x y
p q ,
,
:

z= x

p+ q+ 1

q
p+ q+ 1 .

6.120 x y ,
p
q .. 1. .
x 0 y 0 ,

, z = xy 2 .

94